Man and nature: an Islamic perspective - Abdul Razak, Mohd Abbas (Peshawar Islamicus, 2014)
The topic on man and nature has always been discussed over the centuries and has earned the attention of many scholars of diverse fields of specializations. As an appreciation to the great contribution of nature to human survival, some have equated it to God. Since the two are synonymous to them, so they worship nature alongside God. Others thought nature to be an obstacle to human life and hence needs to be conquered and prevailed upon. In the light of these two extreme positions, this paper intends to investigate the relationship between man and nature from the Islamic perspective. Apart from that, this paper would like to find out as to why the Muslim community is not paying due attention to conservation and preservation of nature at a time when there is a serious call made by others to stop the ongoing environmental degradation that is happening all over the world. It is hoped that an investigation of this nature would bring to light as to what should be the ideal relationship of man with nature from the Islamic perspective.